2019
DOI: 10.2109/jcersj2.19152
|View full text |Cite
|
Sign up to set email alerts
|

Preparation procedure for the electrode slurries of polymer electrolyte fuel cells utilizing the irreversibility of ionomer adsorption onto Pt–C particles

Abstract: The effect of slurry preparation for polymer electrolyte fuel cells on the electrode performance has been investigated in this work. The amount of ionomer adsorbed onto PtC powder increases when water is used as a solvent; however, the size of non-adsorbed ionomer particles increases as well, resulting in a larger gas permeation resistance. Meanwhile, increasing the ethanol-to-water mass ratio in a mixed solvent decreases the ionomer size. Therefore, an improved two-step slurry preparation procedure utilizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Recently, a few groups intensively attempted to control the microstructure of CLs by adding alcohols in catalyst inks. Takahashi et al investigated the influence of the microstructure of CLs tuned by using mixed solutions of 1-propanol and water on the cell performance through the structural observation by cryo-SEM and laser diffraction coupled with qualitative electrochemical analysis . They found that catalyst inks prepared in three different solutions with different water/1-propanol ratios result in the formation of differently sized agglomerates of the Pt/C electrocatalysts interconnected by ionomers; cross-sectional cryo-SEM images indicated that larger agglomerates and pores were formed in CLs prepared from a water-rich solution, than those from an alcohol-rich solution.…”
Section: Introductionmentioning
confidence: 61%
“…Recently, a few groups intensively attempted to control the microstructure of CLs by adding alcohols in catalyst inks. Takahashi et al investigated the influence of the microstructure of CLs tuned by using mixed solutions of 1-propanol and water on the cell performance through the structural observation by cryo-SEM and laser diffraction coupled with qualitative electrochemical analysis . They found that catalyst inks prepared in three different solutions with different water/1-propanol ratios result in the formation of differently sized agglomerates of the Pt/C electrocatalysts interconnected by ionomers; cross-sectional cryo-SEM images indicated that larger agglomerates and pores were formed in CLs prepared from a water-rich solution, than those from an alcohol-rich solution.…”
Section: Introductionmentioning
confidence: 61%
“…15 Thus, the investigation of the ink sedimentation dynamics provides additional information for understanding the solvent-dependent ink structure dynamics. In this study, the AC approach using a 29 700 EW PFSA ionomer in NPA/Water (half blue triangle, 0.32 mg ml −1 ), 6 Nafion DE1021 in EtOH/Water (half green diamond, 50-53 mg ml −1 ), 30 Nafion D521 in DPG/Water (open pink diamond, ∼10 mg ml −1 ), 7 Aquivion PW79S in DPG/Water (half orange star, ∼10 mg ml −1 ). 31 (e) Comparison of the PSDs of catalyst dispersions: Pt/C in NPA/Water (black circle, 9.24 wt%, this work), Vulcan carbon in NPA (red square cross, 0.1 wt%), 16 Vulcan carbon in NPA/Water (blue triangle cross, 0.1 wt%), 32 and Fe-N-C PGM-free in NPA/Water (open orange pentagon, 5 wt%).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous research groups have explored the impact of solvents with varying dielectric constants such as npropanol, [9c] dipropylene glycol, [44] water/propanol, [45] and water/ethanol. [46] Variations in solvent dielectric constants can induce distinct ionomer morphologies in solutions, consequently affecting ionomer microstructures within the electrode. These structures can manifest in three forms based on the dielectric constant: precipitation (for dielectric constants < 3), colloidal dispersion (for dielectric constants between 3 and 10), and dissolution (for dielectric constants > 10).…”
Section: Electrode Ink Formulationmentioning
confidence: 99%
“…The state of ionomers in inks is closely linked to the interactions between ionomers and solvents. Numerous research groups have explored the impact of solvents with varying dielectric constants such as n‐propanol, [9c] dipropylene glycol, [44] water/propanol, [45] and water/ethanol [46] . Variations in solvent dielectric constants can induce distinct ionomer morphologies in solutions, consequently affecting ionomer microstructures within the electrode.…”
Section: Meso/macro Scale Analysismentioning
confidence: 99%